Code of civil procedure, 1908 (act 5 of 1908) as amended by the mediation act, 2023 (act 32 of 2023) along with state amendments and letters patent (Delhi Law & Justice, 2025)
Civil Procedure Code along with State Amendments, Letters Patent, High Court Amendments, Act and Orders.
Keywords: Law-CPC; Code of Civil Procedure